2016
DOI: 10.1007/s12182-016-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

Waxes in asphaltenes of crude oils and wax deposits

Abstract: Composition and molecular mass distribution of n-alkanes in asphaltenes of crude oils of different ages and in wax deposits formed in the borehole equipment were studied. In asphaltenes, n-alkanes from C 12 to C 60 were detected. The high molecular weight paraffins in asphaltenes would form a crystalline phase with a melting point of 80-90°C. The peculiarities of the redistribution of high molecular paraffin hydrocarbons between oil and the corresponding wax deposit were detected. In the oils, the high molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…Elevation of these values results in pressure drop, gelation, lower flowability, and higher pumping cost [3,4]. Waxes are mostly aliphatic and nonpolar compounds which have a high molecular weight, limited solubility in crude oil, and can aggregate or associate in solution [5,6]. The wax deposited in pipelines and tubing may create costly separation problems.…”
Section: Introductionmentioning
confidence: 99%
“…Elevation of these values results in pressure drop, gelation, lower flowability, and higher pumping cost [3,4]. Waxes are mostly aliphatic and nonpolar compounds which have a high molecular weight, limited solubility in crude oil, and can aggregate or associate in solution [5,6]. The wax deposited in pipelines and tubing may create costly separation problems.…”
Section: Introductionmentioning
confidence: 99%
“…During the transportation of crude oil in the subsea region, where the average temperature can be as low as 5°C near the seabed, the liquid-phase waxy crude oil undergoes three phase changes (Chala et al 2018). With the change in the operating conditions (temperature and/or pressure), the wax particles aggregate within the cluster (Ganeeva et al 2016). When the size of the clusters is large enough, the wax precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they are one of the most important constituents of crude oils because they have a great influence on crude oil properties. For analytical purposes, the concentration of asphaltene in a crude oil is defined by precipitation with either n ‐pentane (nC 5 ) or n ‐heptane (nC 7 ) (Ganeeva, Yusupova, & Romanov, ). Evaluation of the amounts of asphaltenes in different oils showed that the asphaltene content were 0.05 and 1.87 wt% for Khanken and Basrah, respectively.…”
Section: Resultsmentioning
confidence: 99%